Ingeniería Industrial: El desafío de aprender a la distancia - Perez, Juan Andrés (2020)
The public health emergency context caused by the COVID-19 Pandemic and Preventive and Mandatory Social Isolation, has forced the Education Sector in general, and the University Sector in particular, to replace the available resources, tools and methodologies, in order to promote the continuity of their pedagogical academic activities. Students, as fundamental and central actors of the university community, are carrying out the situation with hard to quantify efforts, in a context of generalized uncertainty and fear, also conditioned by their own possibilities and limitations. Due to this new reality, was detected the necessity of carrying out an investigation focused on collecting and analyzing the perceptions of Industrial Engineering students from the National University of Luján, with the purpose of contributing to the redesigning and adaptation of teaching-learning practices under virtual reality. Consequently, a field investigation took place in order to understand the scope and limitations of virtual modality implementation on the development of academic Industrial Engineering activities, as well as the insights about contents and disciplinary approaches. Therefore, an ad-hoc data collection instrument (form / questionnaire) was designed to gather the relevant information from active students from the career. Survey’s results allow us to affirm that course lessons under virtual reality are possible which have powerful advantages, but there still unsolved aspects, such as Internet connection and students access to it, as well as the availability of technology and physical space at home. Additionally, teaching practices, contents and methodologies deserve careful attention. The need to balance synchronous and asynchronous work, meanwhile, is positioned as a key strategy to enable student’s permanence and reduce the dropout rate of academic activities.